Research on Design and Implementation of Smart Energy System in Digital Economy Era - Lele, Wang; Wentao, Xu; Guobin, Wang; Hui, Liu; Jing, An; Xiaochuang, Wang; Jun, Ma (2021 International Conference on Artificial Intelligence and Electromechanical Automation (AIEA), 2021)
Digital economy is an economic form that directly or indirectly uses data to guide resources to play a role and promote productivity development. In the era of digital economy, energy system has entered the form of smart energy. As the main part of energy Internet, integrated energy system realizes the transformation of various energy forms and the interconnection of various energy networks, which is one of the key research directions in the future. Smart energy system includes infrastructure layer, data support layer, basic software layer, application system layer, display layer and service object layer. The core modules of smart energy management platform include five major businesses: energy monitoring, energy regulation, energy analysis, energy operation and asset management. This paper designs the modules of smart energy system, and carries out the implementation and test, which provides reference for the relevant researchers.